Pengaruh Pemahaman Ekosistem Digital dan Personality Traits terhadap Minat Mahasiswa Berwirausaha Digital: (Pada Mahasiswa Akuntansi di Universitas dengan Misi Enterpreneurship) - Nikita Aprilia Sukmawidjaya; Dian Anita Nuswantara (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to examine the influence of digital ecosystem understanding represented by Digital Literacy, FinTech Literacy, and AI Literacy as well as personality traits based on the Big Five Personality model on accounting students’ intention to engage in digital entrepreneurship at an entrepreneurship oriented university. This research employs a quantitative approach using primary data collected through purposive sampling. A total of 100 undergraduate accounting students participated by completing Likert scale questionnaires. Data analysis was conducted using a two stage approach including outer model evaluation to ensure validity and reliability followed by inner model assessment to test the proposed hypotheses. The results reveal that digital ecosystem variables including Digital Literacy, FinTech Literacy, and AI Literacy have a positive and significant effect on students’ intention to engage in digital entrepreneurship. Additionally personality traits including Openness to Experience, Conscientiousness, Extraversion, and Agreeableness also show positive and significant influences. In contrast Neuroticism has a negative and significant effect on digital entrepreneurial intention. Simultaneously all independent variables explain 73.4% of the variance in digital entrepreneurial intention indicating strong predictive power. This study integrates external factors represented by the digital ecosystem and internal factors represented by personality traits into a comprehensive framework. Future research is suggested to adopt a longitudinal approach to examine whether these intentions lead to actual entrepreneurial behavior.